Cassaine Diterpenoid Amide from Stem Bark of Erythrophleum fordii Suppresses Cytotoxic and Induces Apoptosis of Human Leukemia Cells - Tu Thanh Thi Nguyen; Dao Cuong To; Phuong Hien Thi Vo; Thanh Hoa Tran; Phi Hung Nguyen; Hien Minh Nguyen; Manh Hung Tran (Molecules, 2020)
Cassaine diterpenoids amides from the stem bark of Vietnamese Erythrophleum fordii Oliver were screened for their cytotoxic activity against human cancer cells. The cell proliferation assay results showed that, among the active compounds, 3β-acetyl-nor-erythrophlamide (3AEP) exhibited the most potential cytotoxicity against human leukemia HL-60 and KG cells with IC50 values of 12.0 ± 1.2 and 18.1 ± 2.7 µM, respectively. Treatment of 3AEP resulted in the apoptosis of HL-60 cells via the activation of caspase 3, and poly (ADP-ribose) polymerase (PARP). Molecular docking in silico results showed that the 3AEP can bind to both the procaspase-3 allosteric site and the PARP-1 active site, with binding energies of −7.51 and −9.63 kcal/mol respectively. These results indicated that the stem bark of Vietnamese E. fordii and its cassaine diterpenoid amides may be useful in the apoptosis induction of human leukemia cancer cells.